Structural performance of a wood-sand-wood wall for blast protection. (15th September 2020) - Hussein, Assal; Heyliger, Paul; Mahmoud, Hussam
Highlights: A simple blast protection wall system composed of wood and sand are designed. Open-space blast tests are conducted to measure the blast pressure distribution in free-air. We developed a 3D dynamic finite element model of the WSaW wall. The experimental results are analyzed and validated with the numerical analysis results. The WSaW wall showed a good capability to resist blast load and provide the required level of protection at low cost. Abstract: In recent years, a noticeable increase in the number of suicide bombing attacks has been noticed. These incidents have targeted civilians and civil infrastructure leaving numerous victims and huge losses in property. Residential complexes and commercial buildings are generally not designed to resist abnormal loads such as explosions. Blast wall systems, also known blast barriers, have been required to mitigate the destructive effects of blast wave in regions where they are most likely to occur. The present study considers the response of a wood-sand-wood (WSaW) blast wall as an example of low-cost blast walls made of readily available materials that can be installed with minimal effort to be used around individuals houses when threat of terrorist attacks is probable. The performance of this WSaW blast wall under blast loading was evaluated experimentally. An open-space blast test was conducted to measure the distribution of blast pressure around/behind the WSaW wall as well as its response. The test results were compared with the results of finite element simulations. The WSaW wall showed significant promise in mitigating the blast wave energy. This study recommends further exploration of WSaW blast walls to potentially reduce casualties and losses in properties in different attack scenarios. Moreover, it is important to draw the attention of researchers and designers to start investigating the performance of simple blast walls made of other readily available materials since it is an urgent need in most areas threatened by terrorism.